Understanding Metrics for Communicating the Economic Importance of Florida’s Fisheries Part II: Quantifying Market Activity - Robert Botta; Christa D. Court; Andrew Ropicki; Edward V. Camp (EDIS)
Florida’s fish and fisheries are vital to the state’s economy, but often people want or need to know just how economically important they are. However, “economic importance” means different things depending on what economic approaches are used. Understanding these differences is important for discussing the economic importance of fisheries and how they might be affected by management actions or environmental changes. This publication is the second part in a three-part series that summarizes different types of economic metrics and how they are often used in a fisheries context. The first publication in the series, , provides an overview and explains how economic measures can be subdivided into two main groups: 1) those that quantify market activity, and 2) those that measure economic value. This second publication focuses on how regional economic methods are used to quantify market activity. It provides a discussion of the most relevant terms and analyses, as well as a brief discussion of how one might proceed with a regional economic analysis that would provide these types of measures for Florida’s fisheries (and related aspects like aquaculture or coastal resources). This information should help readers, especially management agencies and extension agents, as well as the interested public, better understand the metrics associated with quantifying market activity.